Burden of Suicidal Ideation and Attempt among Persons Living with HIV and AIDS in Semiurban Uganda - Godfrey Zari Rukundo; Brian Leslie Mishara; Eugene Kinyanda (AIDS Research and Treatment)
Although the impact of HIV/AIDS has changed globally, it still causes considerable morbidity and mortality, including suicidality, in countries like Uganda. This paper describes the burden and risk factors for suicidal ideation and attempt among 543 HIV-positive attending two HIV specialized clinics in Mbarara municipality, Uganda. The rate of suicidal ideation was 8.8% (n=48; 95% CI: 6.70–11.50) and suicidal attempt was 3.1% (17, 95% CI 2.00–5.00). The factors associated with increased risk for suicidal ideation and attempts were state anger (OR = 1.06, 95% CI: 1.03–1.09; p=0.001); trait anger (OR 1.10, 95% CI 1.04–1.16, p=0.002); depression (OR 1.13, 95% CI 1.07–1.20, p=0.001); hopelessness (OR 1.12, 95% CI 1.02–1.23, p=0.024); anxiety (OR 1.06, 95% CI 1.03–1.09); low social support (OR 0.19, 95% CI 0.07–0.47, p=0.001); inability to provide for others (OR 0.19, 95% CI 0.07–0.47, p=0.001); and stigma (OR 2.48, 95% CI 1.11–5.54, p=0.027). At multivariate analysis, only state anger remained statistically significant. HIV/AIDS is associated with several clinical, psychological, and social factors which increase vulnerability to suicidal ideation and attempts. Making suicide risk assessment and management an integral part of HIV care is warranted.